Business process improvement methodology adoption for improving service quality: case studies of financial institutions in Thailand - Buavaraporn, Nattapan (2010)
To stay competitive and sustain long-term profitability, Business Process Improvement (BPI) methodologies have become strategically important for financial institutions in recent years. These include well-known approaches such as Total Quality Management (TQM), Business Process Reengineering (BPR), Six Sigma and Lean. The customer-focused themes of BPI should be of particular interest to service practitioners, in order to achieve both process excellence and superlative customer service. The adoption of BPI in the financial services sector, however, still appears to be at an early stage. There is limited empirical research reported in the academic literature. This research therefore explored the existing phenomena of BPI adoption through case studies, carried out in leading Thai financial institutions.